О хроматическом числе натуральных арифметичских графов - Донец, А.Г.; Шулинок, Г.А. (Теорія оптимальних рішень, 2007)
The paper was devoted to investigation of chromatic number in numerical graphs. Continuing previous investigations for natural modular graphs this paper focus on natural arithmetical graphs. Eveluation of chromatic number for some classes of natural arithmetical graphs was provided. A number of proposition for cromatic number was given.